2013
DOI: 10.1063/1.4861044
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Non-monotonic supersaturation dependence of the nucleus size of crystals with anisotropically interacting molecules

Abstract: Communication: Multicanonical entropy-like solution of statistical temperature weighted histogram analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…As illustrated in Figure 2, no fibrils can nucleate when the peptide concentration C < C e , whereas for C > C 1β the fibril nucleus is a single peptide and fibrils form in the absence of any nucleation barrier 4,10,11,45,50,51 . Importantly, for intermediate concentrations, C e < C < C 1β , fibril nucleation and elongation depends on their thickness 41 . Despite the fundamental importance of those expressions, they have not yet been verified by neither simulations nor experiments.…”
Section: Peptide Modelmentioning
confidence: 99%
“…As illustrated in Figure 2, no fibrils can nucleate when the peptide concentration C < C e , whereas for C > C 1β the fibril nucleus is a single peptide and fibrils form in the absence of any nucleation barrier 4,10,11,45,50,51 . Importantly, for intermediate concentrations, C e < C < C 1β , fibril nucleation and elongation depends on their thickness 41 . Despite the fundamental importance of those expressions, they have not yet been verified by neither simulations nor experiments.…”
Section: Peptide Modelmentioning
confidence: 99%
“…Recent simulation and theoretical studies of fibril nucleation have highlighted that introducing an interaction anisotropy in these models results in a non-standard nucleation mechanism where the concept of a well-defined nucleus size breaks and nuclei with varying size are observed instead. [62][63][64] B. Pre-equilibrium kinetic models of spontaneous fibril nucleation Worth mentioning at this point are pre-equilibrium kinetic models of fibril nucleation, which often correspond to direct polymerization mechanisms. These models are characterized by two main assumptions.…”
Section: A Direct Polymerization Models Of Spontaneous Fibril Nucleat...mentioning
confidence: 99%
“…Two-step nucleation of polymorphic fibrils, and fibril polymorphism that occurs during fibril growth, or is determined by fibril growth, are not considered. Recently, our simulations showed that amyloid fibril nucleation occurring by direct polymerization of monomers is a peculiar kind of nucleation that does not comply with standard nucleation theory (45,46), because the concept of the existence of a critical nucleus breaks down (the nucleus size does not have a unique value) and there exist jumps in the nucleation rate of many orders of magnitude at certain concentrations (47,48). This called for the development of a new description of amyloid fibril nucleation that is able to describe this nonstandard nucleation of amyloid fibrils (30,49).…”
Section: Introductionmentioning
confidence: 99%